Kinetics of the interaction of sulfate and hydrogen phosphate radicals with small peptides of glycine, alanine, tyrosine and tryptophan - Bosio, Gabriela Natalia (2005)
The kinetics and mechanism of the oxidation of Glycine (Gly), Alanine (Ala), Tyrosine (Tyr), Tryptophan (Trp) and some di-(Gly-Gly, Ala-Ala, Gly-Ala, Gly-Trp, Trp-Gly, Gly-Tyr, Tyr-Gly), tri-(Gly-Gly-Gly, Ala-Gly-Gly) and tetrapeptides (Gly-Gly-Gly-Gly) mediated by sulfate (SO44 •−) and hydrogen phosphate (HPO4−) and hydrogen phosphate (HPO4 •−) radicals was studied, employing the flash-photolysis technique. The substrates were found to react with sulfate radicals (SO4 employing the flash-photolysis technique. The substrates were found to react with sulfate radicals (SO4 −) radicals was studied, employing the flash-photolysis technique. The substrates were found to react with sulfate radicals (SO44 •−, produced by photolysis of the S2O8 2−) faster than with hydrogen phosphate radicals (HPO4 2−) faster than with hydrogen phosphate radicals (HPO4 by photolysis of the S2O8 2−) faster than with hydrogen phosphate radicals (HPO4 2−) faster than with hydrogen phosphate radicals (HPO4 −, produced by photolysis of the S2O8 2−) faster than with hydrogen phosphate radicals (HPO4 2−) faster than with hydrogen phosphate radicals (HPO4 2O8 2−) faster than with hydrogen phosphate radicals (HPO4−) faster than with hydrogen phosphate radicals (HPO4 •−, generated by photolysis of P2O8 4− 4− −, generated by photolysis of P2O8 4−− at pH = 7.1). The reactions of the zwitterions of the aliphatic amino acids and peptides with SO4= 7.1). The reactions of the zwitterions of the aliphatic amino acids and peptides with SO4 •− radicals take place by electron transfer from the carboxylate moiety to the inorganic radical, whereas those of the HPO4 by electron transfer from the carboxylate moiety to the inorganic radical, whereas those of the HPO4 − radicals take place by electron transfer from the carboxylate moiety to the inorganic radical, whereas those of the HPO44 •− proceed by H-abstraction from the a carbon atom. The phenoxyl radical of Tyr-Gly and Gly-Tyr are formed as intermediate species of the oxidation of these peptides by the inorganic radicals. The radical cations of Gly-Trp and Trp-Gly (at pH = 4.2) and their corresponding deprotonated forms (at pH = 7) were detected as intermediates species of the oxidation of these peptides with SO4 oxidation of these peptides with SO4 species of the oxidation of these peptides by the inorganic radicals. The radical cations of Gly-Trp and Trp-Gly (at pH = 4.2) and their corresponding deprotonated forms (at pH = 7) were detected as intermediates species of the oxidation of these peptides with SO4 oxidation of these peptides with SO4 H-abstraction from the a carbon atom. The phenoxyl radical of Tyr-Gly and Gly-Tyr are formed as intermediate species of the oxidation of these peptides by the inorganic radicals. The radical cations of Gly-Trp and Trp-Gly (at pH = 4.2) and their corresponding deprotonated forms (at pH = 7) were detected as intermediates species of the oxidation of these peptides with SO4 oxidation of these peptides with SO4 species of the oxidation of these peptides by the inorganic radicals. The radical cations of Gly-Trp and Trp-Gly (at pH = 4.2) and their corresponding deprotonated forms (at pH = 7) were detected as intermediates species of the oxidation of these peptides with SO4 oxidation of these peptides with SO4 − proceed by H-abstraction from the a carbon atom. The phenoxyl radical of Tyr-Gly and Gly-Tyr are formed as intermediate species of the oxidation of these peptides by the inorganic radicals. The radical cations of Gly-Trp and Trp-Gly (at pH = 4.2) and their corresponding deprotonated forms (at pH = 7) were detected as intermediates species of the oxidation of these peptides with SO4 oxidation of these peptides with SO4 species of the oxidation of these peptides by the inorganic radicals. The radical cations of Gly-Trp and Trp-Gly (at pH = 4.2) and their corresponding deprotonated forms (at pH = 7) were detected as intermediates species of the oxidation of these peptides with SO4 oxidation of these peptides with SO4 a carbon atom. The phenoxyl radical of Tyr-Gly and Gly-Tyr are formed as intermediate species of the oxidation of these peptides by the inorganic radicals. The radical cations of Gly-Trp and Trp-Gly (at pH = 4.2) and their corresponding deprotonated forms (at pH = 7) were detected as intermediates species of the oxidation of these peptides with SO4 oxidation of these peptides with SO4 = 4.2) and their corresponding deprotonated forms (at pH = 7) were detected as intermediates species of the oxidation of these peptides with SO44 •− and HPO4− and HPO4 •−. Reaction mechanisms which account for the observed intermediates are proposed. intermediates are proposed. −. Reaction mechanisms which account for the observed intermediates are proposed.